Chromosome-level genome assembly and annotation of the native Chinese wild blueberry Vaccinium bracteatum - Lu Yang; Minghui Li; Min Shen; Sijia Bu; Bo Zhu; Feng He; Xiaoping Zhang; Xuan Gao; Jiaxin Xiao (Fruit Research, 2022)
Vaccinium bracteatum Thunb., an important native Chinese wild blueberry species, is widely used as a rootstock and in blueberry cultivar breeding, as well as in traditional medicine and local food. We report here the genome sequence of V. bracteatum using a combination of Oxford Nanopore Technologies long-read and Illumina HiSeq short-read sequencing technologies to obtain 65.30 Gb of clean data, achieving 114.60-fold genome coverage. The assembled genome has a total sequence length of 569.81 Mb and consists of 36,756 predicted genes. Repetitive DNA sequences represent 57.78% of the genome sequence. Comparative genomic analysis revealed that a total of 336 gene families had expanded and that 298 candidate genes had undergone positive selection during evolution in V. bracteatum. The divergence of V. bracteatum from the related Rhododendron williamsianum and Rhododendron delavayi occurred ~13−85 million years ago. The genome sequence of V. bracteatum allowed us to identify some important genes associated with traits involved in fruit development, such as flavonoid biosynthesis, sugar and acid metabolism, MYB transcription factor gene expression, and hormone regulation. The differential expression patterns of genes encoding flavonoid biosynthesis enzymes and MYB transcription factors might explain the high flavonoid content of V. bracteatum. This chromosome-level genome assembly provides reference sequences for the identification and characterization of genes important in the improvement of blueberry and related research.